An Ontology for the In-Between of Motion: Aristotle’s Reaction to Zeno’s Arguments - Michel Crubellier (Wydział Filozoficzny UAM, 2021)
This paper proposes an interpretation of Books V and VI of Aristotle’s Physics as being (at least partly) a reaction to Zeno’s four “arguments against motion” that Aristotle expounds and discusses in Phys. VI 9. On the basis of a detailed textual analysis of that chapter, I show that Zeno’s arguments rest on a frame of a priori notions such as part and whole, in contact, between, limit, etc., which Aristotle takes over in order to account for the inner structure (here called “the In-Between”) common to all facts of motion and change. That frame allows him to develop a specific ontology for that inner structure – although it exists only potentially according to the Aristotelian orthodoxy – because he needs such an ontology in order to vindicate the reality of motion and change.
Keywords: Aristotle; Aristotle’s Physics; change; continuous dialectic; infinite motion; ontology; time; Zeno of Elea